Pendampingan One Day One Surah Sebelum Belajar Siswa SMAN 3 Palangka Raya - Yanti, Febry; Azis, Abdul; Norsiyah, Norsiyah (Al-DYAS, 2024)
The Qur'an serves as the primary guide for Muslims, providing guidance and values that need to be internalized in daily life. Reading skills of the Qur'an are very important; however, many students at SMAN 3 Palangka Raya still face difficulties in reading fluently. The aim of this community service is to enhance the students' ability to read the Qur'an through memorizing surahs that are recited before starting lessons via the One Day One Surah program. This program encourages students to read one surah every day, allowing them to master 30 surahs in a month. The method used in this service is Service Learning (SL), which is an approach based on direct experience. The results of this service indicate a significant improvement in students' Qur'an reading abilities after the One Day One Surah assistance was implemented. This is evidenced by the post-test data from class XI-9 obtained after the program was conducted, which shows that the number of students able to recite 22 surahs increased from 15 students, while those who could only recite 15 surahs decreased to 5 students. Furthermore, there was an increase in surah memorization in class XI-10, with data showing that the number of students able to recite 22 surahs rose to 16 students, while those who could only recite 15 surahs decreased to 3 students.